2017
DOI: 10.1128/iai.00475-16
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase Attenuates Pathogen Clearance during Plasmodium yoelii Nonlethal Infection

Abstract: Myeloperoxidase (MPO), a leukocyte-derived enzyme mainly secreted by activated neutrophils, is known to be involved in the immune response during bacterial and fungal infection and inflammatory diseases. Nevertheless, the role of MPO in a parasitic disease like malaria is unknown. We hypothesized that MPO contributes to parasite clearance. To address this hypothesis, we used Plasmodium yoelii nonlethal infection in wild-type and MPO-deficient mice as a murine malaria model. We detected high MPO plasma levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 60 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…Neutrophil elastase and PR3 were increased in malaria from each Plasmodium species and across disease severity, and they are known mediators of acute lung injury in murine malaria models [19] and vascular damage in vitro [33]. Myeloperoxidase, which was elevated only in severe falciparum malaria, has been linked to impaired parasite clearance [34]. Uncontrolled malarial neutrophil activation impairs function [3537], reduces chemotaxis [9], compromises endothelial integrity [13, 38, 39], and has been associated with cerebral vasculopathy in children with cerebral malaria [14] and liver damage in vivax malaria [15].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil elastase and PR3 were increased in malaria from each Plasmodium species and across disease severity, and they are known mediators of acute lung injury in murine malaria models [19] and vascular damage in vitro [33]. Myeloperoxidase, which was elevated only in severe falciparum malaria, has been linked to impaired parasite clearance [34]. Uncontrolled malarial neutrophil activation impairs function [3537], reduces chemotaxis [9], compromises endothelial integrity [13, 38, 39], and has been associated with cerebral vasculopathy in children with cerebral malaria [14] and liver damage in vivax malaria [15].…”
Section: Discussionmentioning
confidence: 99%
“…Placental levels of MPO, MMP9, and PRTN3 all positively correlate with placental parasitemia as well as placental hemozoin bearing WBCs, suggesting that production is enhanced by chronic infection. Since MPO attenuates pathogen clearance during P. yoelii nonlethal infection ( 85 ), it is tempting to speculate that this enzyme may inhibit parasite clearance in PM as well. In an initial pilot study, we found placental blood MPO levels to be increased significantly with chronic, inflammatory PM in primigravidae.…”
Section: Discussionmentioning
confidence: 99%
“…MPO and neutrophils have been implicated in the pathogenesis of falciparum malaria. A recent study of Plasmodium yoelii non-lethal infection in wild-type and MPO deficient mice as a murine malaria model, suggested that MPO could contribute to a protective anti-parasite response [24]. However, very few studies have analyzed MPO levels in human falciparum malaria.…”
Section: Discussionmentioning
confidence: 99%